Skin findings of dialysis patients with chronic renal failure in Afyonkarahisar and surrounding area - Guder, SEMİH; GUDER, SEMİH; Karaca, Semsettin; Kulac, Mustafa; Yuksel, Seref; Guder, Husna (My University, 2012)
Background and Design: To evaluate the prevalence of skin changes in patient with chronic renal failure undergoing hemodialysis.